PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA GURU (Studi Korelasi Pada Guru SD Swasta Gugus 5 Kecamatan Serpong Kota Tangerang Selatan) - Yanto Sugianto Yanto Sugianto; Lili Nurlaili Lili Nurlaili; Ruknan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The purpose of this study is to examine and analyze the influence of transformational leadership, organizational culture, and work motivation on the performance of private elementary school teachers in Cluster 5, Serpong District, which is empirically valid and significant. The approach in this study uses a quantitative method with an associative research methodology aimed at determining causal relationships between variables. The subjects of this research are teachers within Cluster 5, Serpong District, South Tangerang City, for the 2025/2026 academic year, with a total sample of 107 respondents selected through proportional random sampling technique. The data collection instrument used is a questionnaire with a 5-point Likert scale. Before use, the instrument underwent a calibration procedure by calculating its validity and reliability using the SPSS program. Data analysis techniques consist of simple linear regression analysis, multiple linear regression analysis, and prerequisite tests including tests for normality, linearity, multicollinearity, heteroscedasticity, and autocorrelation. The results showed that: (1) There is a positive and significant influence of transformational leadership on teacher performance with a t-count value of 20.701 > t-table 1.982, contributing 80.3%. (2) There is a positive and significant influence of organizational culture on teacher performance with a t-count value of 15.312 > t-table 1.982, contributing 69.1%. (3) There is a positive and significant influence of work motivation on teacher performance with a t-count value of 16.710 > t-table 1.982, contributing 72.6%. (4) Simultaneously, there is a significant influence of transformational leadership, organizational culture, and work motivation on teacher performance with the regression equation Ŷ = 11.192 + 0.541X1 + 0.218X2 + 0.317X3, an F-count value of 222.533 > F-table 2.69, providing a combined contribution of 86.6%, while the remaining 13.4% is influenced by other factors outside this research model.